The per-protocol effect of immediate versus deferred antiretroviral therapy initiation. (13th November 2016) - Lodi, Sara; Sharma, Shweta; Lundgren, Jens D.; Phillips, Andrew N.; Cole, Stephen R.; Logan, Roger; Agan, Brian K.; Babiker, Abdel; Klinker, Hartwig; Chu, Haitao; Law, Matthew; Neaton, James D.; et al.
Abstract : Supplemental Digital Content is available in the text Abstract : Objective: The Strategic Timing of AntiRetroviral Treatment (START) trial found a lower risk of a composite clinical outcome in HIV-positive individuals assigned to immediate initiation of antiretroviral therapy (ART) compared with those assigned to deferred initiation. However, 30% of those assigned to deferred initiation started ART earlier than the protocol specified. To supplement the published intention-to-treat (ITT) effect estimates, here we estimate the per-protocol effect of immediate versus deferred ART initiation in START. Design: The START trial randomized 4685 HIV-positive participants with CD4 + cell counts more than 500 cells/μl to start ART immediately after randomization (immediate initiation group) or to wait until the CD4 + cell count dropped below 350 cells/μl or an AIDS diagnosis (deferred initiation group). Methods: We used the parametric g-formula to estimate and compare the cumulative 5-year risk of the composite clinical outcome in the immediate initiation group, and deferred initiation groups had all the trial participants adhered to the protocol. Results: We estimated that the 5-year risk of the composite outcome would have been 3.2% under immediate ART initiation and 7.0% under deferred initiation. The difference of 3.8% (95% confidence interval 1.5, 6.5) was larger than the ITT effect estimate of 3.1%, corresponding to a difference in effect estimates of 0.72% (−0.35, 2.35). Conclusion: The ITT effect estimate may underestimate the benefit of immediate ART initiation by 23%. This estimate can be used by patients and policy-makers who need to understand the full extent of the benefit of changes in ART initiation policies.